Higher vascular plant abundance associated with decreased ecosystem respiration after 20 years of warming in the forest-tundra -ecotone ... - Myrsky, Eero; Mikola, Juha; Kaarlejärvi, Elina; Olofsson, Johan; Sjögersten, Sofie; Tupek, Boris; Mannisto, Minna; Stark, Sari (Dryad, 2023)
The ongoing climate warming is promoting shrub abundance in high latitudes, but the effect of this phenomenon on ecosystem functioning is expected to depend on whether deciduous or evergreen species increase in response to warming. To explore effects of long-term warming on shrubs and further on ecosystem functioning, we analyzed vegetation and ecosystem CO2 exchange after 20 years of warming in the forest-tundra ecotone in sub-arctic Sweden. A previous study conducted nine years earlier had found increased evergreen Empetrum nigrum ssp. hermaphroditum in the forest and increased deciduous Betula nana in the tundra. Following current understanding, we expected a continued increase in shrub abundance that would be stronger in tundra than in forest. We expected warming to increase ecosystem respiration (Re) and gross primary productivity (GPP), with a greater increase in Re in tundra due to increased deciduous shrub abundance, leading to a less negative net ecosystem exchange (NEE) and reduced ecosystem C sink ... : Vegetation analyses The plant community composition was earlier recorded in 1999 and 2009 in five control plots and five OTCs in both habitats (Kaarlejärvi et al. 2012). We used the same plots during the present investigation and analyzed the composition of vegetation in July 2018 with the point intercept method: in OTCs, a total of 87 pins was systematically distributed among three diagonals of the hexagons, 29 pins per diagonal. For each pin, the total number of hits as well as the height of the highest hit were recorded for each plant. Only one hit for each species was counted at the ground layer for each pin. The same method was applied to control plots. Later the total number of hits was normalized to hits per 100 pins. Data from one forest plot was discarded because of poor plot condition. Ecosystem carbon flux analyses For the ecosystem carbon flux analyses, we included a few additional plots to have seven plots per treatment in the forest and eight plots per treatment in the tundra. The fluxes were ...